Building resilience beyond the crisis. Issue 2 (1st June 2021) - Ros-Cuéllar, Julia; Koff, Harlan; Maganda, Carmen; Kauffer, Edith
Abstract : April 2021 is here, one year and a month after the World Health Organization (WHO) declared a state of emergency for the COVID-19 pandemic. The vaccines have arrived, bringing us closer to the end of this crisis, but COVID-19 is not gone; therefore, the call for action remains relevant. We want to take this opportunity to remember and embrace the emphasis that has been put on the need for joint efforts and coordinated strategies, so we can thrive together, bringing everyone on board irrespective of geographic, economic, and political differences.